Information theory and thermodynamic properties for a combined potential model - C. A. Onate; B. B. Deji-jinadu; O. O. Ajani; J. A. Akinpelu; O. Ebomwonyi (Scientific Reports)
Abstract Yukawa potential and Hulthẻn potential are very useful potential models with applications in different areas of physics. The present study examined theoretic measure and thermodynamic properties of energy levels and wave functions for a combination of these two potentials. The effect of screening parameter on Fisher information and Shannon entropy as well as the effect of temperature on the various thermodynamic properties of the combined potentials and its subsets potentials are well studied. The effects of screening parameter on the thermodynamic properties of the combined potentials are also studied. This study shows equivalence of temperature effect on the combined potential and Hulthẻn potential but a different effect on Yukawa potential. Fisher information and the Shannon entropy for both position and momentum spaces as a function of the screening parameter obey Heisenberg principle, satisfy Cramer-Rao inequality and Bialynick-Birula, Mycielski inequality. The Shannon entropy shows the stability of the system for low screening parameter. It is also shown that the strength of Hulthẻn potential outweighed the strength of Yukawa potential in their combination for thermodynamic properties.